ANALISIS PERATURAN MENTERI PENDIDIKAN, KEBUDAYAAN, RISET, DAN TEKNOLOGI REPUBLIK INDONESIA NOMOR 63 TAHUN 2023: IMPLIKASI TERHADAP PROGRAM PENINGKATAN KUALITAS PENDIIDK DAN TENAGA KEPENDIDIKAN SDN SINDANGSARI KECAMATAN PASEH KAB BANDUNG - Dwi Yulia, Mira; Wasliman, Iim; Andriana Gaffar, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is entitled “Analysis of the Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 63 of 2023: Implications for the Quality Improvement Program for Educators and Education Personnel of SDN Sindangsari Kec Paseh Kab Bandung This study aims to determine and analyze: 1) Planning, 2). Organizing, 3). Implementation, 4). Evaluating, 5). This research uses a qualitative approach with descriptive methods. Data collection was carried out using triangulation techniques using interviews, document studies, and field observations. Planning recommendations are suggested to be supported by adequate student resources so that the improvement of resources and competence of students can increase by conducting periodic trainings to produce continuous improvement. It is recommended that students continue to improve their competencies, including pedagogical, social, personality and professional competencies. Keywords: minister of education regulations, quality of educators, education personnel